The Teachers’ Perception and Attitude on Curriculum Changes in Indonesia toward High School Biology Learning in Lamongan Regency - Patekur, Patekur; Wulandari, Tabitha Sri Hartati; Panggabean, Christina Innocenti Tumiar (International Journal of Education Research and Development, 2022)
The purpose of this study is to describe the perception and attitude of teachers on curriculum changes in Indonesia in view of high school Biology learning in Lamongan Regency. The research applied descriptive quantitative research design. Research subjects’ number 40 high school biology teachers in Lamongan. Data was collected by online questionnaire with Google Form. Data were analyzed by percentage statistics. The results of this study showed that the perception and attitude of the teachers on curriculum changes related to the planning of learning implementation was 55% in high category. Meanwhile, the teachers’perception on curriculum changes related to the learning process of Biology was 100% in moderate category. The perception of the teachers on curriculum changes related to the assessment of Biology learning was 87,5% in very high category. It can be concluded that the perception and attitude of teachers on curriculum changes were considered positive. However, it is suggested that the policy makers and the practitioners of education to improve the quality of Biology learning process in accordance with the applicable curriculum. For other researchers to focus more on the perceptions and attitudes of teachers on curriculum changes in terms of the implementation of the biology learning process.